PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS BAHAN DAUR ULANG - Mal Alfahnum; Maya Masitha Astriani (Jurnal Abdimas Bina Bangsa, 2024)
Early childhood and kindergarten are a unique person, who has a very large curiosity and has a strong desire to imitate and try all the stimuli or stimuli in the environment. To support child development, it is expected that teachers who have the skills and creativity to provide stimulus with learning media, this is so that children grow in accordance with their development. This community service activity aims to improve the competence of early childhood education teachers (PAUD) and kindergartens (TK) in making learning media made from recycled materials that can provide knowledge and experience for students. The method used is lecture, practice of making learning media and peer teaching using learning media. The results obtained by the teacher's creativity increased, the number of learning media in PAUD and TK institutions increased after attending the training